AN CORRELATION STUDY BETWEEN ENGLISH LANGUAGE TEACHERS’ CLASSROOM MANAGEMENT AND STUDENTS’ MOTIVATION IN JOINING THE CLASS - Chomar Nur Machmut; Dias Andris Susanto; T Sri Suwarti (Wawasan Pendidikan, 2023)
This final project studies “the correlational study between english language teachers’ classroom management and students’ motivation in joining the class”. The aims of this study are: (1) To measure the correlation between teachers’ classroom management and students’ motivation in joining the class (2) To find out whether there is significant correlation between teacher classroom management and student motivation. Quantitative approach was used in this study. The design of the research was quantitative design by using questionnaire as the research instrument. The population of this research was the students of SMAN 2 Grabag. The writer took 33 students from class XI MIPA 1 and 28 students from class XII IPS 3 as the sample. The result of this study shows that; a) the score result of the correlation coefficient was -,096, it means that the correlation between those two variables were very low ; b) The gap of the correlation between two variable is not rally related. It can be seen in the result of correlation coefficient was -,096 and minimum correlation score 0,000 -0,200 it means that correlation coefficient was lower than minimum correlation. Teachers can improve students’ motivation in joining the class by using another method or maybe by involving the newest development.